Tinjauan Yuridis Keberadaan Saksi Sebagai Whistleblower dan Justice Collaborators Pada Tindak Pidana Korupsi - Suwito, Eddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
This study discusses the juridical review of the existence of witnesses as a whistleblower and justice collaborators on criminal acts of corruption. In order to deal with the increasingly rampant problems of corruption, the government also needs to carry out extra ordinary treatment, tenacity and active participation and to be able to break the chain of conspiracy of corruption. One form of corruption prevention that has been the subject of discussion in the past year is the existence of whistle blowers and justice collaborators. This study uses a type of normative juridical research supported by the statute approach. Then it can be concluded as follows: a. The Power of Proof of Witness Whistleblower and Justice Collaborators on Corruption Crimes Reports submitted by whistleblowers can be used as evidence if he is a witness in criminal justice. Information on justice collaborator and whistleblower is evidence of witnesses that can be submitted at the investigation or trial stage., b. The Contribution of Whistleblower Witness and Justice Collaborators in Corruption Crimes, The presence of a whistle blower and justice collaborator in uncovering corruption cases that occur in the surrounding environment is very helpful in the examination process from the investigation stage to the examination stage in the Court so that the existence of the two can indirectly provide a little convenience for the Police, Prosecutors, and other legal agencies in uncovering criminal offenses as an inseparable part of our Criminal Justice System